“God does not algebra”: Simone Weil’s search for a supernatural reformulation of mathematics - Roberto Paura (Labyrinth: An International Journal for Philosophy, Value Theory and Sociocultural Hermeneutics, 2024)
The article offers an analysis of Simone Weil's philosophy of mathematics. Weil's reflection starts from a critique of Bourbaki's programme, led by her brother André: the "mechanical attention" Bourbaki considered an advantage of their treatment of mathematics was for her responsible for the incomprehensibility of modern algebra, and even a cause of alien-ation and social oppression. On the contrary, she developed her pivotal concept of 'atten-tion' with the aim of approaching mathematical problems in order to make "progress in another more mysterious dimension". In the Pythagorean 'crisis of incommensurables', Weil saw the possibility of defining the relationships between things in terms that are not exclusively numerical. This implies drawing an analogy between mathematical relation-ships and God's relationship with mankind (logos), the basis of a 'supernatural' reformu-lation of the entire scientific understanding of the world. The consequence is a critique of machinism and the possibility to contrast algorithmic reason with a "supernatural reason".